A supported polyolefin catalyst and its preparation method and application
By using a combination of mesoporous ZSM-23 molecular sieve support, metal halide and Group 3 transition metal, a supported polyolefin catalyst was prepared, which solved the problems of low reaction activity and serious environmental pollution in low-carbon olefin polymerization reaction, and achieved efficient, stable and selective polymerization reaction.
Patent Information
- Application Number
- CN202111243480.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-10-25
AI Technical Summary
The prior art has problems such as low reaction activity, wide product distribution, poor selectivity, and serious environmental pollution in low-carbon olefin polymerization reaction.
Mesoporous ZSM-23 molecular sieve was used as a support to introduce metal halides and Group 3 transition metals, and a supported polyolefin catalyst was prepared by drying and calcining.
It improves the reactive activity, stability and product selectivity of olefin polymerization, reduces environmental pollution, reduces process costs, and conforms to the concept of green development.
Smart Images

Figure CN116023561B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a supported polyolefin catalyst and a preparation method and application thereof, and more particularly to a supported catalyst suitable for low-carbon olefin polymerization and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of my country's economy, China's ethylene production capacity has grown rapidly, making it the world's second largest ethylene producer after the United States. The C4 and C5 fractions produced as byproducts of ethylene cracking units account for about 40-50wt.% of ethylene production, respectively. The olefin content is more than 50%, and the olefins contained have considerable potential for deep processing. In addition to producing medium and high polyisobutylene, they can also produce high value-added isoparaffin solvent oil through oligomerization and hydrogenation. Therefore, how to reasonably utilize the C4 and C5 olefin resources produced as byproducts of ethylene cracking has gradually attracted people's attention, which is of great significance to petrochemical enterprises in tapping potential and increasing efficiency and developing fine chemicals.
[0003] At present, polyisobutylene usually uses anhydrous aluminum chloride as a catalyst. Anhydrous aluminum chloride is dissolved in hydrocarbons and mixed with isobutylene for homogeneous reaction. This homogeneous reaction usually uses a traditional stirred tank reactor. When the reaction is about to start, the catalyst and the raw materials are not evenly mixed, which will cause isobutylene to react violently with the area with high catalyst concentration, and the reaction heat cannot be diffused and temperature rises. There are problems such as low product yield, wide product distribution, and poor selectivity. This homogeneous method also has low production efficiency and difficulty in product separation. At the same time, aluminum chloride is highly corrosive, polluting the environment and corroding equipment. Therefore, the development of new environmentally friendly immobilized catalysts for olefin polymerization has attracted much attention in recent years.
[0004] USP4929800 uses CCl4, CH3Cl or CH2Cl2 as solvents, dissolves aluminum chloride in them, and then adds carriers such as silicon oxide or aluminum oxide, and refluxes for several hours or days at 50~80℃ under N2 protection conditions to obtain olefin polymerization catalysts. This method is relatively simple using a solution method, but due to the low solubility of the solvent in aluminum chloride, and the loading degree of aluminum chloride depends on the pore structure and size of the carrier. Therefore, this method has low aluminum chloride loading efficiency and low polymerization reaction activity, and also causes waste of aluminum chloride raw materials and pollutes the environment.
[0005] CN107159278A relates to a method for preparing a supported oxide catalyst. The method mainly uses macroporous alumina as a carrier, and supports iron sulfate and nickel sulfate to prepare a finished catalyst. The catalyst requires mild reaction conditions, but the method has problems such as different molecular chain lengths of the polymerized product, wide product distribution, and low selectivity.
[0006] CN1398833 discloses a method for preparing a solid phosphoric acid catalyst for propylene polymerization, which comprises preparing 72-88% (by weight) polyphosphoric acid at 120-180°C in a copper reactor, preparing phosphate at 150-230°C, and then mixing with diatomaceous earth, extruding into strips, drying, roasting, and activating. The catalyst preparation cycle is long, and the conversion rate of the solid phosphoric acid catalyst is not high, and the catalyst stability is poor.
[0007] CN102240563 discloses an olefin polymerization catalyst with Al2O3 as a carrier and AlCl3 and a Group VIII transition metal salt as active components. The catalyst is used to catalyze the polymerization reaction of 1-decene or 1-octene, overcoming the problems of strong corrosiveness of aluminum chloride and difficulty in product separation. However, the catalyst has the problems of low catalytic activity and poor stability.
[0008] ZSM-23 molecular sieve is a molecular sieve material with a high silicon-aluminum ratio and an MTT topological structure. Its one-dimensional teardrop-shaped pores are composed of ten-membered rings. With its unique pore structure and adjustable acid properties, ZSM-23 molecular sieves are widely used in the fields of separation, adsorption and catalysis, playing an irreplaceable role. However, ZSM-23 is a microporous molecular sieve, and its ability to process the conversion of larger molecules is limited by the pore size. Therefore, in order to further expand its application range, it is of great significance to prepare mesoporous ZSM-23 molecular sieves with excellent performance. Summary of the invention
[0009] In order to overcome the deficiencies in the prior art, the present invention provides a supported polyolefin catalyst and a preparation method and application thereof. The catalyst is suitable for the polymerization reaction of low-carbon olefins such as isobutylene and isopentene, and has the advantages of high reaction activity, easy product separation, and reduced environmental pollution.
[0010] A method for preparing a supported polyolefin catalyst comprises the following steps: a mesoporous ZSM-23 molecular sieve or a mesoporous ZSM-23 molecular sieve formed and then introduced with a metal halide and / or a first The final supported polyolefin catalyst is obtained after drying and calcination.
[0011] In the method of the present invention, the preparation method of the supported polyolefin catalyst comprises the steps of kneading a mesoporous ZSM-23 molecular sieve, a binder and an adhesive, and preparing the catalyst carrier after drying and calcining; and loading a metal halide and / or a first catalyst carrier on the obtained catalyst carrier. The transition metal of group A is dried and calcined to prepare the final supported polyolefin catalyst.
[0012] In the method of the present invention, the preparation method of the supported polyolefin catalyst specifically comprises the following steps:
[0013] (1) Preparation of mesoporous ZSM-23 molecular sieve;
[0014] (2) The mesoporous ZSM-23 molecular sieve prepared in step (1) or the mesoporous ZSM-23 molecular sieve formed and then introduced with metal halide and the The final supported polyolefin catalyst is obtained after drying and calcination.
[0015] In the method of the present invention, the preparation of the mesoporous ZSM-23 molecular sieve in step (1) comprises the following steps:
[0016] a. Prepare or select amorphous silicon dioxide;
[0017] b. treating amorphous silicon dioxide with alkali;
[0018] c. ZSM-23 molecular sieve is prepared using alkali-treated amorphous silica as a silicon source.
[0019] In step a of the above method, the amorphous silicon dioxide has a specific surface area of 600-1300m 2 / g, preferably 700-1200m 2 / g; pore volume is 0.6-1.3cm 3 / g, preferably 0.7-1.2cm 3 / g; the pore diameter is 1-15nm, preferably 2-10nm.
[0020] In step a of the above method, the amorphous silica preparation process is as follows: adding a silicon source to deionized water and dispersing it evenly, then adding a surfactant and stirring; adjusting the solution pH to 1-5, preferably 1.5-4, and heating it in a water bath for a period of time; filtering, washing, drying, and calcining to obtain amorphous silica.
[0021] In the above method, during the preparation of amorphous silicon dioxide, the silicon source is an inorganic silicon source, preferably one or more of water glass, silica sol or white carbon black.
[0022] In the above method, during the preparation of amorphous silicon dioxide, the surfactant is one or more of hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, and octadecyltrimethylammonium bromide.
[0023] In the above method, during the preparation of the amorphous silica, the molar ratio of the silicon source in terms of SiO2 to the surfactant is 1:(0.02-0.3), preferably 1:(0.05-0.2).
[0024] In the above method, during the preparation of the amorphous silicon dioxide, the molar ratio of the silicon source in terms of SiO2 to deionized water is 1:(30-300), preferably 1:(50-220).
[0025] In the above method, during the preparation of the amorphous silica, the heating temperature is 30-80°C, preferably 40-70°C, and the heating time is 0.5-8h, preferably 3-6h.
[0026] In step b of the above method, the alkali treatment is to add the amorphous silicon dioxide prepared in step a into an alkaline solution and heat and stir.
[0027] In the above method, the alkali treatment adopts inorganic alkali treatment, and the inorganic alkali is one or more of sodium hydroxide, potassium hydroxide or ammonia water.
[0028] In the above method, the alkali treatment heating and stirring time is 0.5-12h, preferably 2-8h; the heating temperature is 25-60°C, preferably 30-50°C.
[0029] In the above method, the molar ratio of amorphous silica calculated as SiO2 to the inorganic base is 0.05-0.24, preferably 0.06-0.22.
[0030] In step c of the above method, in preparing ZSM-23 molecular sieve using alkali-treated amorphous silicon dioxide as a silicon source, any method for preparing ZSM-23 molecular sieve known in the prior art may be used, and a method for preparing ZSM-23 molecular sieve that is not yet known in the prior art but will be known in the future may also be used. For example, a known method is disclosed in U.S. Pat. No. 4,990,342 of Mobil Oil Corporation.
[0031] In step c of the above method, preferably, alkali-treated amorphous silicon dioxide is used as a silicon source, and the silicon source is mixed with an aluminum source, an alkali source (MOH), a template (R), and water to form a gel, and the ZSM-23 molecular sieve is obtained after crystallization, filtration, washing, drying, and calcination;
[0032] More preferably, the molar ratio of silicon source (in terms of SiO2): aluminum source (in terms of Al2O3): alkali source (in terms of hydroxide): template: H2O in the gel is 1: (0.003-0.03): (0.03-0.3): (0.05-2): (10-90); further preferably, the molar ratio of silicon source (in terms of SiO2): aluminum source (in terms of Al2O3): alkali source (in terms of hydroxide): template: H2O in the gel is 1: (0.005-0.02): (0.03-0.16): (0.08-1.6): (20-70);
[0033] More preferably, the gel is crystallized at 150-200°C, preferably 170-180°C, for 24-96h, preferably 36-72h, and then filtered, washed, dried, and calcined to obtain a ZSM-23 molecular sieve; and / or
[0034] More preferably, the drying temperature is 80-120° C., the drying time is 4-12 hours, the roasting temperature is 500-600° C., and the roasting time is 2-6 hours.
[0035] In the above method, the prepared mesoporous ZSM-23 molecular sieve has a pore size of 3-8nm, preferably 3-6nm, and the mesopore volume accounts for 45-90% of the total pore volume of the molecular sieve, preferably 50-85%, and further preferably 55-81%; the relative crystallinity of the molecular sieve is 95-120%, and the relative crystallinity retention of the molecular sieve after hydrothermal treatment with water vapor at 600°C for 2 hours is 95-100%.
[0036] In step (2) of the method of the present invention, the mesoporous ZSM-23 molecular sieve prepared in step (1), the binder and the peptizing agent are mechanically mixed and formed, and then dried at a temperature of 80-150° C. for 2-10 hours and calcined at 500-600° C. for 3-6 hours to prepare a catalyst carrier. The catalyst carrier can be formed according to actual needs and the shape can be cylindrical, clover, etc.
[0037] In the above method, the alumina used can be small-pore alumina, and the pore volume of the small-pore alumina used is 0.3-0.5 ml / g, and the specific surface area is 200-400 m 2 / g. The binder used may be one or more of aluminum sulfate, citric acid, nitric acid, acetic acid, oxalic acid, etc.
[0038] In step (2) of the method of the present invention, the metal halide is AlCl3 or TiCl4. Based on the weight percentage of the final catalyst, the final catalyst contains 0.1wt% to 20wt% of the metal halide, preferably 1wt% to 15wt%.
[0039] In step (2) of the method of the present invention, the The transition metal of the first group is Fe, Co, or Ni. The catalyst contains the following: The amount of the transition metal oxide is 1wt% to 35wt%, preferably 2wt% to 8wt%.
[0040] In step (2) of the method of the present invention, a metal halide and a The transition metals of group I are impregnated by equal volume impregnation or volume impregnation. The transition metals can be impregnated in separate steps or in combination.
[0041] In step (2) of the method of the present invention, firstly introduce A transition metal salt is then introduced into the metal halide. The specific method of preparing transition metal salts is as follows: at 20-60°C, a mesoporous ZSM-23 molecular sieve is added to a 0.1-2.0 M The precipitate is immersed in the nitrate of transition metal Fe, Co, or Ni for 1 to 4 hours, and then vacuum dried at 60 to 120°C for 1 to 6 hours. It is then calcined at 200 to 600°C for 4 to 12 hours.
[0042] The specific method of introducing metal halide is as follows: the metal halide is mixed with a solvent to form a solution, wherein the metal halide is preferably AlCl3 or TiCl4, and the solvent is selected from any one of CCl4, tetrahydrofuran or ethanol, and the concentration of the solution is 1% to 10%, preferably 2% to 6%. Then the metal halide solution is added to the introduction Finally, the immobilized catalyst was obtained by vacuum drying at 80-150℃ for 3-10h.
[0043] In step (2) of the method of the present invention, the drying conditions are as follows: the drying temperature is 60°C to 180°C, preferably 90°C to 120°C, and the drying time is 0.5h to 20.0h, preferably 3.0h to 6.0h; the calcination conditions are as follows: the calcination temperature is 200°C to 750°C, preferably 500°C to 650°C, and the calcination time is 0.5h to 20.0h, preferably 3.0h to 6.0h. The drying and calcination can be carried out in an oxygen-containing atmosphere, with no particular limitation on the oxygen concentration, such as an air atmosphere, or in an inert atmosphere, such as a nitrogen atmosphere.
[0044] A supported polyolefin catalyst prepared by the above method, comprising a mesoporous ZSM-23 molecular sieve, an active component comprising a metal halide and a second The specific surface area of the catalyst is 230-400m 2 / g, pore volume is 0.31-0.5cm 3 / g, micropore specific surface area is 40-150m 2 / g, mesopore specific surface area is 140-300m 2 / g; preferably, the specific surface area is 260-345m 2 / g, pore volume is 0.34-0.45cm 3 / g, micropore specific surface area is 60-120m 2 / g, mesopore specific surface area is 161-265m 2 / g.
[0045] The above catalyst contains 30wt% to 80wt% of ZSM-23 molecular sieve, preferably 50wt% to 70wt% of ZSM-23 molecular sieve, based on the final supported polyolefin catalyst; The content of the transition metal oxide is 1wt%~35wt%, preferably 2wt%~8wt%; and the content of the metal halide is 0.1wt%~20wt%, preferably 1wt%~12wt%.
[0046] The supported polyolefin catalyst is used in a fixed bed reactor to carry out olefin polymerization reaction with isobutylene or isopentene as raw material; the process conditions are: reaction temperature of 40-120°C, pressure of 1.0-6.0MPa, volume space velocity of 0.6-1.5h -1 .
[0047] Compared with the prior art, the method of the present invention has the following advantages:
[0048] (1) The ZSM-23 molecular sieve synthesized by the method of the present invention has both the acidic properties of the microporous structure that can be adjusted and the macroporous characteristics of the mesoporous structure, and has stable catalytic performance, further improving the reaction activity, stability and product selectivity of the olefin polymerization reaction.
[0049] (2) The present invention uses a new catalyst combining active metal, solid superacid and molecular sieve, which has higher acid content and acid strength, and further improves the conversion rate and reaction efficiency of olefin polymerization reaction.
[0050] (3) The present invention solves the problems of corrosion of traditional low-carbon olefin polymerization reaction equipment, high chlorine content of products, and environmental pollution caused by wastewater generated by catalyst post-treatment. It saves energy and reduces consumption, can significantly reduce process costs, and is in line with the concept of green development. DETAILED DESCRIPTION
[0051] In order to better illustrate the present invention, the following is further described in conjunction with embodiments and comparative examples, but the present invention is not limited to these embodiments.
[0052] The analysis method of the present invention is as follows: The specific surface area and pore volume of the catalyst or molecular sieve are measured by using an ASAP 2405 physical adsorption instrument from Micromeritics, USA, where the specific surface area refers to the sum of the micropore specific surface area and the mesopore specific surface area. The loaded metal content is measured by atomic absorption spectroscopy.
[0053] The XRD spectrum of the sample was obtained by a Dmax2500 X-ray diffractometer produced by Rigaku Corporation of Japan, and the relative crystallinity of the sample was calculated. The sum of the heights of the diffraction peaks at 2θ of about 11.3 and 19.5-23° in the XRD spectrum of conventional ZSM-23 molecular sieve was taken as 100% crystallinity, and the relative crystallinity of other samples was obtained by comparison.
[0054] Embodiment 1:
[0055] (1) Preparation of carrier:
[0056] Add 50g of water glass (SiO2 mass fraction is 27%) to 250g of deionized water, stir and disperse evenly, then add octadecyl trimethyl ammonium chloride (C 18 TMAC1) was stirred for 0.5h, wherein SiO2 and C 18 The molar ratio of TMACl was 1:0.08; the pH of the solution was adjusted to 2 with hydrochloric acid, and then placed in a 50°C water bath and heated for 4 hours; after completion, the solution was filtered, washed, dried at 80°C for 8 hours, and calcined at 550°C for 3 hours to obtain amorphous silica;
[0057] Dissolve 0.35 g of NaOH in 35 mL of deionized water, add 3.7 g of the prepared mesoporous silicon source, and stir in a 45 °C water bath for 3 h;
[0058] After aluminum sulfate and isopropylamine (IPA) are dissolved in the remaining water in sequence, the silicon source dispersion obtained in a) is added thereto to obtain a total molar ratio of SiO2 in the silicon source: Al2O3 in the aluminum source: OH - :IPA:H2O=1:0.01:0.08:1.0:50 gel, after crystallization at 180°C for 48h, filtered, washed, dried and calcined, to obtain ZSM-23 molecular sieve, the properties of which are as follows: the specific surface area of the molecular sieve is 395m 2 / g, pore volume is 0.42cm 3 / g, micropore specific surface area is 105m 2 / g, mesopore specific surface area is 290m 2 / g, the mesoporous content of pore size 3-8nm is 77%, the relative crystallinity is 102%, and the relative crystallinity after hydrothermal treatment is 103%.
[0059] The ZSM-23 molecular sieve, small pore alumina and binder were mechanically mixed and formed, and then dried at 120°C for 8 hours and calcined at 600°C for 4 hours to prepare a catalyst carrier. The small pore alumina used has a pore volume of 0.5 ml / g and a specific surface area of 300 m 2 / g.
[0060] (2) Preparation of catalyst:
[0061] 300 g of the carrier was added to 1.0 M ferric nitrate solution, stirred evenly, soaked at 30° C. for 3 h, and then vacuum dried at 70° C. for 3 h. Then, calcined at 500° C. for 8 h.
[0062] 40g of anhydrous aluminum chloride was dissolved in 2000ml of tetrahydrofuran, and then 50g of the support was mixed with the solution and kept at reflux temperature for 12h. Finally, the supported catalyst was dried at 120°C in vacuum for 6h to obtain the supported catalyst.
[0063] Through analytical characterization, the specific surface area of the catalyst is 298m 2 / g, pore volume is 0.43cm 3 / g, micropore specific surface area is 73m 2 / g, mesopore specific surface area is 226m 2 / g. The composition of the catalyst is as follows: the content of aluminum chloride in the supported catalyst is 3.50wt%, the content of iron oxide in the catalyst is 3.55wt%, and the mass content of ZSM-23 molecular sieve is 65.3%.
[0064] (3) Olefin polymerization reaction:
[0065] Using isobutylene as raw material, polymerization reaction was carried out in a small fixed bed reactor with a catalyst loading volume of 40 ml and a volumetric space velocity of 1.0 h -1 , the reaction temperature is 80°C, the pressure is 4.0MPa, and the product distillation range distribution and isobutylene conversion rate are shown in Table 1.
[0066] Embodiment 2:
[0067] 300 g of the carrier in Example 1 was added to a 0.5 M ferric nitrate solution, stirred evenly, soaked at 30° C. for 5 h, and then vacuum dried at 70° C. for 3 h, and then calcined at 500° C. for 8 h.
[0068] 20g of anhydrous aluminum chloride was dissolved in 2000ml of tetrahydrofuran, and then 50g of the support was mixed with the solution and kept at reflux temperature for 12h. Finally, the supported catalyst was dried under vacuum at 120°C for 6h to obtain the supported catalyst.
[0069] Through analytical characterization, the specific surface area of the catalyst is 312m 2 / g, pore volume is 0.43cm 3 / g, micropore specific surface area is 79m 2 / g, mesopore specific surface area is 233m 2 / g. The composition of the catalyst is as follows: the content of aluminum chloride in the supported catalyst is 1.66wt%, the content of iron oxide in the catalyst is 2.23wt%, and the mass content of ZSM-23 molecular sieve is 68.5%.
[0070] Using isobutylene as raw material, polymerization reaction was carried out in a small fixed bed reactor. The reaction conditions were the same as those in Example 1. The product distillation range distribution and isobutylene conversion rate are shown in Table 1.
[0071] Embodiment 3:
[0072] 300 g of the carrier in Example 1 was added to a 1.5 M ferric nitrate solution, stirred evenly, soaked at 30° C. for 5 h, and then vacuum dried at 70° C. for 3 h, and then calcined at 500° C. for 8 h.
[0073] 60g of anhydrous aluminum chloride was dissolved in 2000ml of tetrahydrofuran, and then 50g of the support was mixed with the solution and kept at reflux temperature for 12h. Finally, the supported catalyst was obtained by vacuum drying at 120°C for 6h.
[0074] Through analytical characterization, the specific surface area of the catalyst is 285m 2 / g, pore volume is 0.42cm 3 / g, micropore specific surface area is 69m 2 / g, mesopore specific surface area is 216m 2 / g. The composition of the catalyst is as follows: the content of aluminum chloride in the supported catalyst is 4.82wt%, the content of iron oxide in the catalyst is 5.12wt%, and the mass content of ZSM-23 molecular sieve is 64.7%.
[0075] Using isobutylene as raw material, polymerization reaction was carried out in a small fixed bed reactor. The reaction conditions were the same as those in Example 1. The product distillation range distribution and isobutylene conversion rate are shown in Table 1.
[0076] Embodiment 4:
[0077] 300 g of the carrier in Example 1 was added to a 1.0 M nickel nitrate solution, stirred evenly, soaked at 30° C. for 6 h, and then vacuum dried at 80° C. for 3 h, and then calcined at 500° C. for 8 h.
[0078] 40g of anhydrous aluminum chloride was dissolved in 2000ml of tetrahydrofuran, and then 50g of the carrier was mixed with the solution and kept at reflux temperature for 12h. Finally, the solid-supported catalyst was obtained by vacuum drying at 100°C for 8h.
[0079] Through analytical characterization, the specific surface area of the catalyst is 296m 2 / g, pore volume is 0.43cm 3 / g, micropore specific surface area is 71m 2 / g, mesopore specific surface area is 225m 2 / g. The composition of the catalyst is as follows: the content of aluminum chloride in the supported catalyst is 3.52wt%, the content of nickel oxide in the catalyst is 2.26wt%, and the mass content of ZSM-23 molecular sieve is 65.7%.
[0080] Using isobutylene as raw material, polymerization reaction was carried out in a small fixed bed reactor. The reaction conditions were the same as those in Example 1. The product distillation range distribution and isobutylene conversion rate are shown in Table 1.
[0081] Comparative Example 1:
[0082] (1) Preparation of molecular sieves:
[0083] Water glass, aluminum sulfate, isopropylamine (IPA), sodium hydroxide and water were mixed to prepare a gel with a total molar ratio of SiO2 in silicon source: Al2O3 in aluminum source: NaOH: IPA: H2O = 1:0.01:0.08:1.0:50. After heating at 180°C for 72h, the conventional ZSM-23 molecular sieve was obtained after filtering, washing, drying and calcining. The properties of the molecular sieve are as follows: The specific surface area of the molecular sieve is 228m 2 / g, pore volume is 0.24cm 3 / g, micropore specific surface area is 188m 2 / g, mesopore specific surface area is 40m 2 / g, the mesopore content with a pore size of 3-8nm is 18%, the relative crystallinity is 100%, and the relative crystallinity after hydrothermal treatment is 101%.
[0084] Conventional ZSM-23 molecular sieve, small pore alumina and binder were mechanically mixed and formed, then dried at 120°C for 8 hours and calcined at 600°C for 4 hours to prepare a catalyst carrier. The small pore alumina used had a pore volume of 0.5 ml / g and a specific surface area of 300 m 2 / g.
[0085] (2) Preparation of Catalyst
[0086] 300 g of the carrier was added to 1.0 M ferric nitrate solution, stirred evenly, soaked at 30° C. for 3 h, and then vacuum dried at 70° C. for 3 h. Then, calcined at 500° C. for 8 h.
[0087] 40g of anhydrous aluminum chloride was dissolved in 2000ml of tetrahydrofuran, and then 50g of the carrier was mixed with the solution and kept at reflux temperature for 12h. Finally, the solid-supported catalyst was obtained by vacuum drying at 100°C for 8h.
[0088] Through analytical characterization, the specific surface area of the catalyst is 159m 2 / g, pore volume is 0.25cm 3 / g, micropore specific surface area is 126m 2 / g, mesopore specific surface area is 33m 2 / g. The composition of the catalyst is as follows: the content of aluminum chloride in the supported catalyst is 2.56wt%, the content of iron oxide in the catalyst is 2.63wt%, and the mass content of ZSM-23 molecular sieve is 68.3%.
[0089] (3) Olefin polymerization
[0090] Using isobutylene as raw material, polymerization reaction was carried out in a small fixed bed reactor. The reaction conditions were the same as those in Example 1. The product distillation range distribution and isobutylene conversion rate are shown in Table 1.
[0091] Comparative Example 2:
[0092] A conventional ZSM-23 molecular sieve carrier was obtained according to the method of Comparative Example 1.
[0093] 300 g of the carrier in Comparative Example 1 was added to a 1.5 M ferric nitrate solution, stirred evenly, soaked at 30° C. for 5 h, and then vacuum dried at 70° C. for 3 h, and then calcined at 500° C. for 8 h.
[0094] 60g of anhydrous aluminum chloride was dissolved in 2000ml of tetrahydrofuran, and then 50g of the support was mixed with the solution and kept at reflux temperature for 12h. Finally, the supported catalyst was obtained by vacuum drying at 120°C for 6h.
[0095] Through analysis and characterization, the specific surface area of the catalyst is 156m 2 / g, pore volume is 0.25cm 3 / g, micropore specific surface area is 126m 2 / g, mesopore specific surface area is 30m 2 / g. The composition of the catalyst is as follows: the content of aluminum chloride in the supported catalyst is 3.46wt%, the content of iron oxide in the catalyst is 3.57wt%, and the mass content of ZSM-23 molecular sieve is 66.5%.
[0096] Using isobutylene as raw material, polymerization reaction was carried out in a small fixed bed reactor. The reaction conditions were the same as those in Example 1. The product distillation range distribution and isobutylene conversion rate are shown in Table 1.
[0097] Table 1
[0098] <160℃Product yield, % 160℃~340℃ product yield, % >340℃Product yield, % Conversion rate, % Example 1 11.5 80.2 8.3 94.3 Example 2 20.3 76.2 3.5 92.6 Example 3 9.8 78.0 12.2 96.1 Example 4 13.6 75.2 1.2 90.5 Comparative Example 1 52.2 40.6 7.2 69.3 Comparative Example 2 45.7 45.8 8.5 72.5
Claims
1. A method for preparing a supported polyolefin catalyst, characterized in that: The method comprises the following contents: a mesoporous ZSM-23 molecular sieve, a binder and an adhesive are kneaded and formed, and then dried and calcined to form a catalyst carrier; a metal halide and / or a Group VIII transition metal is loaded on the obtained catalyst carrier, and then dried and calcined to form a final loaded polyolefin catalyst; The adhesive is small-pore alumina, the pore volume of the small-pore alumina is 0.3-0.5 ml / g, and the specific surface area is 200-400 m 2 / g, the binder is: one or more of aluminum sulfate, citric acid, nitric acid, acetic acid, and oxalic acid; The preparation of the mesoporous ZSM-23 molecular sieve comprises the following steps: a. Prepare or select amorphous silicon dioxide; b. treating amorphous silicon dioxide with alkali; c. Using alkali-treated amorphous silicon dioxide as a silicon source to prepare ZSM-23 molecular sieve; In step a, the amorphous silicon dioxide has a specific surface area of 600-1300m 2 / g, pore volume is 0.6-1.3cm 3 / g, and the pore diameter is 1-15nm.
2. The method according to claim 1, characterized in that: In step a, the amorphous silicon dioxide has a specific surface area of 700-1200m 2 / g, pore volume is 0.7-1.2cm 3 / g, and the pore diameter is 2-10nm.
3. The method according to claim 1, characterized in that: In step a, the amorphous silicon dioxide preparation process is as follows: adding a silicon source to deionized water and dispersing it evenly, then adding a surfactant and stirring; adjusting the pH of the solution to 1-5, and heating it in a water bath for a period of time; Amorphous silicon dioxide is obtained after filtering, washing, drying and calcining.
4. The method according to claim 3, characterized in that: The solution pH was adjusted to 1.5-4.
5. The method according to claim 1, characterized in that: In step b, the alkali treatment is to add the amorphous silicon dioxide prepared in step a into an alkaline solution and heat and stir.
6. The method according to claim 1, characterized in that: In step c, ZSM-23 molecular sieve is prepared by using alkali-treated amorphous silicon dioxide as a silicon source.
7. The method according to claim 1, characterized in that: The prepared mesoporous ZSM-23 molecular sieve has a pore volume of 3-8 nm mesopores accounting for 45-90% of the total pore volume of the molecular sieve; the relative crystallinity of the molecular sieve is 95-120%, and the relative crystallinity retention of the molecular sieve after hydrothermal treatment with 600°C steam for 2 hours is 95-100%.
8. The method according to claim 7, characterized in that: The prepared mesoporous ZSM-23 molecular sieve has a pore volume of mesopores with a pore size of 3-6 nm, which accounts for 45-90% of the total pore volume of the molecular sieve.
9. The method according to claim 7, characterized in that: The prepared mesoporous ZSM-23 molecular sieve has a pore volume of mesopores with a pore size of 3-6 nm, which accounts for 50-85% of the total pore volume of the molecular sieve.
10. The method according to claim 7, characterized in that: The prepared mesoporous ZSM-23 molecular sieve has a pore volume of mesopores with a pore size of 3-6 nm, which accounts for 55-81% of the total pore volume of the molecular sieve.
11. The method according to claim 1, characterized in that: The mesoporous ZSM-23 molecular sieve, the binder and the adhesive are mechanically mixed and formed, and then dried at a temperature of 80-150°C for 2-10 hours and calcined at 500-600°C for 3-6 hours to prepare a catalyst carrier, and the shape after forming is a cylindrical bar or a clover.
12. The method according to claim 1, characterized in that: The metal halide is AlCl3 or TiCl4. Based on the weight percentage of the final catalyst, the final catalyst contains 0.1wt% to 20wt% of the metal halide.
13. The method according to claim 12, characterized in that: Based on the weight percentage of the final catalyst, the final catalyst contains 1wt% to 15wt% of metal halide.
14. The method according to claim 1, characterized in that: The Group VIII transition metal is Fe, Co, or Ni. Based on the weight of the final catalyst, the catalyst contains 1 wt%-35 wt% of the Group VIII transition metal oxide.
15. The method according to claim 14, characterized in that: The catalyst contains 2wt%-8wt% of Group VIII transition metal oxide.
16. The method according to claim 1, characterized in that: The metal halide and the Group VIII transition metal are loaded by an impregnation method, wherein the metal halide and the Group VIII transition metal are impregnated step by step or co-impregnated.
17. The method according to claim 1, characterized in that: After the obtained catalyst carrier is loaded with metal halide and / or Group VIII transition metal, the drying conditions are as follows: drying temperature is 60°C-180°C, and drying time is 0.5h-20.0h; calcination conditions are as follows: calcination temperature is 200°C-750°C, and calcination time is 0.5h-20.0h.
18. The method according to claim 17, characterized in that: After the obtained catalyst carrier is loaded with metal halide and / or Group VIII transition metal, the drying conditions are as follows: drying temperature is 90°C-120°C, and drying time is 3.0h-6.0h; calcination conditions are as follows: calcination temperature is 500°C-650°C, and calcination time is 3.0h-6.0h.
19. A supported polyolefin catalyst prepared by the preparation method of any one of claims 1 to 18, comprising a mesoporous ZSM-23 molecular sieve, and the active components are a metal halide and a Group VIII transition metal; the specific surface area of the catalyst is 230-400 m 2 / g, pore volume is 0.31-0.5cm 3 / g, micropore specific surface area is 40-150m 2 / g, mesopore specific surface area is 140-300m 2 / g.
20. The catalyst according to claim 19, characterized in that: The specific surface area of the catalyst is 260-345m 2 / g, pore volume is 0.34-0.45cm 3 / g, micropore specific surface area is 60-120m 2 / g, mesopore specific surface area is 161-265m 2 / g.
21. The catalyst according to claim 19, characterized in that: Based on the final supported polyolefin catalyst, it contains 30wt%-80wt% of ZSM-23 molecular sieve, 1wt%-35wt% of Group VIII transition metal oxide, and 0.1wt%-20wt% of metal halide.
22. The catalyst according to claim 21, characterized in that: Based on the final supported polyolefin catalyst, it contains 50wt%-70wt% of ZSM-23 molecular sieve, 2wt%-8wt% of Group VIII transition metal oxide, and 1wt%-12wt% of metal halide.
23. Use of the supported polyolefin catalyst according to any one of claims 19 to 22 in a fixed bed reactor.
24. The use according to claim 23, characterized in that: Olefin polymerization is carried out using isobutylene or isopentene as raw materials; the process conditions are: reaction temperature is 40-120℃, pressure is 1.0-6.0MPa, volume space velocity is 0.6-1.5h -1 .
Citation Information
Patent Citations
Olefin oligomerization method
CN107159278A
Fungicidal composition with synergistic activity
US4990342A
Supported catalyst for alpha-olefin oligomerization, and preparation and application thereof
CN102240563A
Olefin oligomerization method
CN1489564A
Crystalline zeolite ZSM-23 and synthesis thereof
US4076842A